Securing WSN with lightweight resource-efficient schemes - Pathan, Al-Sakib Khan (LAP LAMBERT Academic Publishing , VDM Verlag, Germany, 2011)
Security in wireless sensor network (WSN) encompasses a great number of challenges; ranging from the nature of wireless communications, constrained resources of the sensors, unknown topologies of the deployed networks, unattended and accessible environment where sensors might be susceptible to physical attacks, dense and large networks, etc. In general, the research areas on security in WSN could be categorized as; (a) Key Management (b) Secure routing and transport, (c) Security services, (deployment strategy, security framework, etc.), (d) Intrusion detection system A single mechanism cannot solve all the issues. Keeping this point in mind, this book deals with security services and secure routing [areas (b) and (c)] in WSN. It analyzes the impact of security mechanisms on the resource efficiency in wireless sensor network.